2020
DOI: 10.3906/sag-1910-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of isothermal amplification method for Mycobacteriumtuberculosisdetection and visualization method for fieldwork

Abstract: Introduction Tuberculosis caused by Mycobacterium tuberculosis is spread from person to person through respiratory fluids and air [1]. M. tuberculosis has a low infective dose; just below the 10 bacilli (1 to 200 bacilli) are enough for infection [2]. Tuberculosis comes right after HIV for infection-caused deaths [3]. According to the World Health Organization (WHO) reports, 1/3 of the world population today is already infected with tuberculosis. It was estimated that 10 million people developed tuberculosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, the commercial colorimetric mix also gave false positive results for EHV-1 when using the primer set described by Nemoto et al [ 19 ], whereas EHV-1 primers designed in this study did not cause any false positive test results. Other studies using this colorimetric method also observed false positive test results, which may have arisen due to primer dimerization, non-specific amplification due to primer design, change of pH or other factors [ 13 , 25 , 26 ]. Moreover, we demonstrated that the LAMP reagents were thermostable at a storage temperature of 4 °C for at least six weeks .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the commercial colorimetric mix also gave false positive results for EHV-1 when using the primer set described by Nemoto et al [ 19 ], whereas EHV-1 primers designed in this study did not cause any false positive test results. Other studies using this colorimetric method also observed false positive test results, which may have arisen due to primer dimerization, non-specific amplification due to primer design, change of pH or other factors [ 13 , 25 , 26 ]. Moreover, we demonstrated that the LAMP reagents were thermostable at a storage temperature of 4 °C for at least six weeks .…”
Section: Discussionmentioning
confidence: 99%
“…The primers were optimized according to the protocol described in the previous study. 23 The LAMP primers consisted of two outer primers (F3 and B3) and two inner primers [FIP (F1c + F2) and BIP (B1c + B2)], and two loop primers [FLP: (forward loop primer) and BLP (backward loop primer)]. 21 For the preparation of samples, the standard strain of M. tuberculosis H37Rv was used.…”
Section: Methodsmentioning
confidence: 99%
“…The limit of detection (LOD) of the M. tuberculosis LAMP test was determined as 10 2 CFU/mL in the previous study. 23 In this study to test whether the DNA hunter device performed the LAMP reaction correctly, five different concentrations (10 1 -10 5 CFU/mL) were studied above and below the LOD limit. A bacteria-free sputum sample was used for negative control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] The coordinated use of Bst 3.0 DNA polymerase and WarmStart™ RTx greatly improves the consistency and specificity of one-step isothermal amplification. 26,27 By optimizing the reaction system and conditions, the amplification of two target genes can be performed at the same reaction temperature using one device. In order to improve the sensitivity of LFIA to fluorescence sensing, functional nanoparticles are used as signal amplifiers.…”
Section: Introductionmentioning
confidence: 99%